Persistent infectious and tropical diseases in immigrant correctional populations - L. Getaz; L. Da Silva-Santos; H. Wolff; M. Vitoria; N. Serre-Delcor; J.C. Lozano-Becerra; F. Chappuis; P. Albajar-Viñas
A number of infectious diseases amongst travelers and the immigrant populations are a major public health concern. Some have a long incubation period or remain asymptomatic or paucisymptomatic for many years before leading to significant clinical manifestations and/or complications. HIV, hepatitis B and C, tuberculosis or latent syphilis are among the most significant persistent diseases in migrants. Schistosomiasis and strongyloidiasis, for instance, are persistent helminthic infections that may cause significant morbidity, particularly in patients co-infected with HIV, hepatitis B and C. Chagas disease, which was initially confined to Latin America, must also now be considered in immigrants from endemic countries. Visceral leishmaniasis and malaria are other examples of parasitic diseases that must be taken into account by physicians treating incarcerated migrants. The focus of this review article is on the risk of neglected tropical diseases in particularly vulnerable correctional populations and on the risk of infectious diseases that commonly affect migrants but which are often underestimated.